The Influence of Life-Friendly Human Resource Policies on Employee Engagement, Work-Life Balance, and Job Satisfaction in the Food and Beverage Industry - Muhammad Juda Kusumah; Dimas Angga Negoro (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
In the Food & Beverage industry, which is characterized by long working hours and a dynamic work environment, maintaining a balance between work and personal life (work-life balance) poses a challenge for employees. This study aims to analyze the impact of life-friendly human resource policies on work-life balance, employee engagement, and job satisfaction. Additionally, it examines the role of employee engagement as a mediator in the relationship between life-friendly human resource policies and work-life balance. This study employs a quantitative method with a Structural Equation Model (SEM) approach, analyzing data from 183 employees at Bangor Berkembang Abadi. Data collection was conducted through an online survey using a purposive sampling technique. Data analysis was performed using SmartPLS 4.0 and SPSS 26 software. The results indicate that life-friendly human resource policies significantly influence work-life balance and employee engagement. Employee engagement also positively affects work-life balance and serves as a mediator in the relationship between life-friendly human resource policies and work-life balance. However, job satisfaction does not significantly impact work- life balance, suggesting that other factors, such as work flexibility and organizational support, play a more crucial role in determining employees’ work-life balance. The implications of this study highlight the need for companies to implement more flexible HR policies, such as flexible work arrangements, fair shift rotations, and employee well-being support, to enhance employee engagement and work-life balance.